ANALISIS KESULITAN MEMBACA PERMULAAN PADA PESERTA DIDIK KELAS II SD NEGERI 4 LUBUKLINGGAU - Tiara Amelia Putri; Vivi Widiana Saputri; Episiasi (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This research aims to describe students' difficulties in beginning reading in class II students at SDN 4 Lubuklinggau. This research was conducted at SDN 4 Lubuklinggau on November 12 2024. Research data was obtained by conducting observations, interviews, questionnaires and documentation regarding the initial reading difficulties of grade II elementary school students. This type of research uses qualitative research. The subjects of this research were class II students and teachers. The results of the study showed that there were several initial reading difficulties experienced by second grade students. Through data from the research results, it can be concluded that the initial reading difficulties of class II students are: students have difficulty reading letters, have difficulty distinguishing letters, students cannot spell syllables, and have difficulty recognizing or understanding punctuation marks. The inhibiting factors for students who have difficulty reading at the beginning are: lack of interest in learning, students not attending kindergarten, and families who do not provide enough learning support.